If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + 73 = -1b + 3 Reorder the terms: 73 + b = -1b + 3 Reorder the terms: 73 + b = 3 + -1b Solving 73 + b = 3 + -1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add 'b' to each side of the equation. 73 + b + b = 3 + -1b + b Combine like terms: b + b = 2b 73 + 2b = 3 + -1b + b Combine like terms: -1b + b = 0 73 + 2b = 3 + 0 73 + 2b = 3 Add '-73' to each side of the equation. 73 + -73 + 2b = 3 + -73 Combine like terms: 73 + -73 = 0 0 + 2b = 3 + -73 2b = 3 + -73 Combine like terms: 3 + -73 = -70 2b = -70 Divide each side by '2'. b = -35 Simplifying b = -35
| -2y+2y=8 | | [x]=-18 | | 12x+36=-2(x) | | 10x-2(x-7)=8(x+1)+7 | | 6-2x+6x=x-3 | | 12x+36=-2(2) | | 4a^2-4a-3=0 | | 2=2x-17 | | (11x-3)+(10x+1)= | | 6x+7=-47-3 | | 12x+36=-2 | | 3x-4-5x=-10 | | 4.6+2.5= | | 1=3x-53 | | 3(x+4)-2x=-11 | | (x-9)=(2x+33) | | (3x+6xy+y^2)dx+(2x^2+3xy)dy=0 | | t*6-6=9 | | 2/3(3x-9)=11 | | 4a+9=2a-6 | | a*4+1=9 | | (3r+7)*2=-34 | | 12x+36=-2x | | -6n-4n=10 | | 9X^2-14X=X+6 | | 9x+1.5=4x+0.6 | | 6b+39=5b+1 | | 5(x-2)=71-4x | | 3(x-4)=36-3x | | 2y+-8x=4 | | 2x-1=119 | | 4x-5=55-8x |